Numerical simulation of a heavy rainfall event over Mindanao, Philippines, on 03 May 2017: mesoscale convective systems under weak large-scale forcing - Cathrene Lagare; Takeshi Yamazaki; Junshi Ito (Geoscience Letters, 2023)
Abstract A heavy rainfall event caused by mesoscale convective systems (MCSs) resulted in flooding over areas of Davao City in Mindanao Island, Philippines, on 03 May 2017. The event occurred during the summer season (April–May) under weak large-scale conditions. This study investigated the initiation and development of MCSs by performing high-resolution numerical simulations with the finest grid spacing of 200 m, using the Weather Research and Forecasting (WRF) model. It was found that the merging of two meso- $$β$$ β scale convective systems over the west and east of Mount Apo caused the flood-producing rainfall in the Davao area. Results show that the west meso- $$β$$ β scale convective system formed over the basin area in Mindanao Island due to moisture advection from sea breeze circulation. In addition, the concave geometry of the Mindanao basin assisted in accumulating moisture which made the basin favorable for convection development. Meanwhile, the precipitating downdrafts generated cold pools wherein the continuous convergence of multiple outflow boundaries resulted in the further development and maintenance of the MCS over the basin. While the east meso- $$β$$ β scale convective system developed over the Davao area due to the interaction between southeasterlies (ambient trade winds) and Mount Apo terrain. Merging of the MCSs resulted in the development of a larger meso- $$β$$ β scale system. Eventually, the larger meso- $$β$$ β scale convective system split and splitted MCSs weakened over time.